contradictions in teaching creative expression (Journal of the College of Basic Education, 2022)
Expression is not a linguistic branch isolated from the rest of the language branches. Rather, it is intertwined and intertwined in its language skills with other branches of language to a large extent. It is intertwined with grammatical and morphological rules, and intertwined with spelling and calligraphy. This means that the student's progress and growth in one of these linguistic branches is the student's progress and growth in all written expression skills.